SHORT-CAM – A USEFUL DELIRIUM SCREENING TOOL IN PALLIATIVE CARE?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Porteous, Anna; Lowery, Lucy; MacCormick, Fiona; Paxton, Ann; Vidrine, Jennifer
Abstract : Background: The short-CAM (Confusion Assessment Method) delirium screening tool is validated in the palliative care setting. As an observational tool it is felt to be acceptable in its ease of use, however, some studies highlight challenges in its implementation. Delirium screening using the short-CAM has been incorporated into routine assessment in five North East Specialist Palliative Care In-patient Units (SPCUs). Aims: To assess staff opinion on the importance of screening for delirium To determine the acceptability of the short-CAM as a screening tool. Methods: Patients admitted to five SPCUs were regularly screened for delirium using the short-CAM. Clinical and allied health professionals participated in multi-disciplinary assessment of patients to inform short-CAM completion. After four months of use, a voluntary and anonymous survey of staff members was conducted. Verbal rating scales were used to record staff experiences of the tool's implementation, their impression of its value and ease of use. Results: Sixty-three doctors, nurses, allied health professionals and administrators completed the survey. Fifty (79%) respondents believed screening for delirium to be important, however, 62% of those involved in using the short-CAM felt it did not always accurately reflect patients' condition. Sixty-four percent of staff members found the short-CAM "not at all" burdensome to complete, however, only 44% felt the short-CAM should be introduced into routine care. Ten percent of respondents did not feel it should be introduced and 46% were unsure. Limitations: Completion was voluntary and time limited, creating potential bias in responders. Conclusions: The majority of health professionals believe screening for delirium to be important in the palliative care setting, however less than half believe the short-CAM should be introduced into routine patient assessment. This is likely to be multi-factorial, relating to paper-work burden, limited perceived impact on patient care and lack of confidence in this tool to reflect a complex patient group.